DEVELOPMENT OF AN ADVANCED GENETIC TOOLBOX TO ENABLE GENOME SCALE ENGINEERING IN SINORHIZOBIUM MELILOTI - MacLeod, Michael R. (My University, 2018)
Synthetic biology has ushered in a new age of molecular biology with the aim towards practical developments in disciplines ranging from medicine, agriculture, and industry. Presently, it remains difficult to manipulate the genomes of many organisms due to lack of genetic tools. These problems can be circumvented by cloning large fragments of DNA into strains where many genetic tools are in place, such as Saccharomyces cerevisiae. However, this organism is unable to directly transfer cloned DNA to other organisms and is unable to stably maintain DNA with a G+C content >40%. Many organisms relevant in biotechnology often have G+C content DNA >60%, and therefore are difficult to engineer. Here, the soil bacteria Sinorhizobium meliloti was chosen as a host strain to clone and manipulate large fragments of high G+C content DNA. S. meliloti is a Gram-negativeα-proteobacteria that forms symbiotic relationships with legumes to fix nitrogen. It has a multi-partite genome with a G+C content of 62.7% that includes a chromosome (3.65 Mb), the pSymA (1.35 Mb), and pSymB (1.68 Mb) replicons. A restriction endonuclease hsdR mutant strain lacking pSymA and pSymB was created and used in this study. Multi-host shuttle (MHS) vectors were constructed that allow for direct transfer and maintenance of DNA in E. coli, S. cerevisiae, and P. tricornutum. Characterization of strains was conducted to determine transduction, conjugation, and transformation frequencies, as well as stability of MHS plasmids. Furthermore, a proof-of-concept experiment was conducted to clone large plasmids (70-205 kb) with G+C content >58% via site-specific recombination at a landing pad in the MHS vector, which was then verified using colony PCR. This work demonstrates the usefulness of S. meliloti containing a MHS vector for cloning of large fragments with high G+C content DNA, a technology that may be used for several applications in both applied and basic research.
Keywords: Synthetic biology; Genetic engineering; high G+C content; Sinorhizobium meliloti; multi-host shuttle vector; site-specific recombination; biotechnology; S. cerevisiae; P. tricornutum